Initial symptoms of patients with coronavirus disease 2019 in Japan: A descriptive study - Komagamine, Junpei (J Gen Fam Med, 2020)
Fever, cough, malaise, and sore throat are the most common initial symptoms of coronavirus disease 2019 (COVID‐19). However, no studies have ever been conducted to investigate the initial symptoms of COVID‐19 in Japan. By using publicly available data, we investigated 707 consecutive COVID‐19 patients who were diagnosed in 10 prefectures of Japan prior to May 16, 2020. The primary outcomes were the initial symptoms on the day of symptom onset. The proportions of patients with each symptom among the symptomatic patients were calculated. Of all the patients, 79 (11.2%) were asymptomatic. Among the 628 symptomatic patients, the most common initial symptom was fever (65.9%), followed by cough (23.5%), malaise (23.5%), and sore throat (12.9%). At least one of these four symptoms was reported in 88.2% of all symptomatic patients. Nineteen patients (3.0%) reported gastrointestinal symptoms without respiratory symptoms, while six patients (1.0%) reported only the loss of smell or taste as the initial symptom. As in other countries, the most common initial symptoms of COVID‐19 in Japan are fever, cough, malaise, and sore throat. Gastrointestinal symptoms without respiratory symptoms and the loss of smell and taste are uncommon initial symptoms in Japan.